Authentic customer centricity : a journey towards sustainable customer experience - Zafer, Alkhatani Saad (Emerald Publishing Limited : Information Age Publishing Inc., 2015)
This book offers a breakthrough formula for creating a sustainable customer centric organization, which forms the key to enduring business success. This new blueprint entails a systematic and integrated journey towards customer centricity.In this book, Dr. Zafer has provided a sorely needed guidebook for executives to become a successful customer centric company. He shows us how companies can deliver a superior customer experience that result in trusted customer relations that can boost profitability. This is the book you should read if you want to deliver a superior customer experience in a sustainable way.